Recursos digitales de la plataforma Educare Ecuador para la asignatura de Química del tercer año de bachillerato general unificado utilizados por los docentes de los colegios de bachillerato y unidades educativas fiscales de la ciudad de Loja en el año lectivo 2021-2022, - Silva Suquilanda, Gabriel Alejandro (2023)
Nowadays in education it is necessary to promote digital learning through training processes, creation and management of virtual resources specially from the health emergency that has arisen worldwide; Facing it, teachers seek to strengthen the teaching-learning process in an integral and holistic manner to provide a quality and kind education. The present Curriculum Integration Work defines the use of the digital resources of the Educar Ecuador platform by the teachers of the Chemistry subject of the third year of the Unified General Baccalaureate (UGB), with an academic basis in the documents of the Ministry of Education, the Agenda Digital, a study by Aliaga (2018) and the Organic Law of Intercultural Education. The methodology used, part of the deductive method, quantitative approach, descriptive / exploratory type, the population considered consisted of 17 educational institutions of fiscal support belonging to Zone 7 of education of the city of Loja in the 2021- 2022 school year. An ad hoc questionnaire based on Aliaga (2018) was created, the same one that was applied through the survey technique based on the Likert scale, the dimensions to be considered for the study are framed in the use of the Educar Ecuador platform, specifically of digital resources; concluding in this way that teachers make occasional use of digital resources and the Educar Ecuador platform; Likewise, it is recommended that the authorities and other educational actors manage continuous training through the Ministry of Education and higher education institutions, with respect to the context researched here. Keywords: Educar Ecuador Platform, Digital Resources, Unified General Baccalaureate Teachers, Chemistry